Analysis of Investigative Services in Disclosing State Financial Losses: A Case Study of the State Assets and Auction Services Office (KPKNL) - Nayla Maulidya Safira; Adryan Gymnastiar; Aryo Andika Supari; Ernawaty Usman; Abdul Kahar (Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the role of the Kantor Pelayanan Kekayaan Negara dan Lelang (KPKNL) in supporting investigative services for uncovering state financial losses. The research employed a descriptive qualitative approach with a case study method through direct observation and interviews conducted at KPKNL. The findings indicate that KPKNL plays a significant role in supporting investigative processes through state asset management, state receivable administration, asset valuation, debtor tracing, field verification, document validation, and the auction of confiscated assets and court-decided properties. In addition, risk management of state receivables is implemented through collection procedures, field examinations, and legal actions against uncooperative debtors. Although KPKNL does not have direct authority to conduct investigations or criminal inquiries, its functions contribute substantially to asset recovery efforts and support transparent and accountable state financial governance. The study concludes that KPKNL serves as an important supporting institution in the process of uncovering and recovering state financial losses.